The role of meaning and life satisfaction in coping with stress during midlife crisis - Nasution, Samsul Bahri; Tjalla, Awaluddin; Liana, Susan; Thohir, Muhammad (Jurnal Ilmiah Psikologi Terapan, 2025)
Growing older is a definite cycle of growth and development in everyone's life. All kinds of joys and pains can be experienced, as the crisis of middle adulthood is a crossroads between the peak of psychological well-being and the stress of stress. This research aims to determine the influence of purpose and life satisfaction as predictors of coping with stress-inducing crises in middle adulthood. This research used a quantitative design with a sample of 96 middle-aged adults aged 40 and over. The research sample was selected using a convenience sampling method through an online questionnaire with multiple linear regression data analysis methods. The instrument for this research uses a meaning in life Scale prepared by researchers based on Frankl's Theory of the meaning in life, the LSI - A Life Satisfaction Scale, and the Stress Scale from the DASS - 42. The results of the study showed that the meaning in life and life satisfaction influence the crisis period of middle-aged adults in coping with stress. (R = 0.653; R² = 0.426; F = 34.557; p < 0.000) using multiple linear regression tests. The effect of purpose in life is not significant with stress (t = 2.132; p = 0.036), life satisfaction is significantly related to stress (t = 8.187; p < 0.000). Facing and coping with crises in middle adulthood therefore requires taking life satisfaction into account when seeking solutions to the stress they cause.